2013
DOI: 10.4284/0038-4038-2012.309
|View full text |Cite
|
Sign up to set email alerts
|

Does Terrorism Affect the Stock‐Bond Covariance? Evidence from European Countries

Abstract: Using daily stock and bond returns data from four European countries—France, Germany, Spain, and Great Britain—that have been the victims of significant terrorist activity, this study addresses the issue of whether transnational and/or domestic terrorist attacks have affected in any significant manner the time‐varying stock–bond covariance, their returns, and their variances. Stock and bond markets can be influenced and determined not only by the usual array of macroeconomic factors but also by security shocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…In a follow up study, Kollias et al (2013a) argue that both equity and bond markets are shaped by terrorist incidents, which trigger a flight-to-safety effect primarily in France and Germany and to a lesser extent in the UK and Spain. Similarly, using a multivariate GARCH model, Kollias et al (2013b) reveal that the covariance between oil returns and the returns of US and leading European equities are also affected by war.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow up study, Kollias et al (2013a) argue that both equity and bond markets are shaped by terrorist incidents, which trigger a flight-to-safety effect primarily in France and Germany and to a lesser extent in the UK and Spain. Similarly, using a multivariate GARCH model, Kollias et al (2013b) reveal that the covariance between oil returns and the returns of US and leading European equities are also affected by war.…”
Section: Related Studiesmentioning
confidence: 99%
“…Unlike, the conventional equity markets, there is very little work on the impact of geopolitical risks on returns and volatilities of conventional bond markets, though there does exist some work on the impact of terror attacks on the comovements of stocks and bonds (see for example, Kollias et al, (2013a); Gupta et al, (2017)). The two studies that we could find were that of Hempel (2016) and Schepers (2016), which tend to indicate the impact of terror attacks on conventional bond returns.…”
Section: Causality Testsmentioning
confidence: 99%
“…Technically speaking, the main advantage of the BEKK-GARCH model is that it guarantees by its construction that the covariance matrices in the system are positive (Engle and Kroner 1995). In addition, the bivariate unrestricted version of the general BEKK(p,q)-GARCH model with p=q=1 is used in order to avoid any serious convergence problems (see, for instance, Bauwens, Laurent, and Rbouts 2006;Kollias, Kyrtsou, and Papadamou 2013;Kollias, Papadamou, and Arvanitis 2013). By assuming Student's t distribution (t), maximum likelihood methodology is used to estimate jointly the parameters of the mean and the variance-covariance equations.…”
Section: The Modelmentioning
confidence: 99%
“…11. For different types of model based on the MGARCH family see, for instance, Kollias, Kyrtsou, and Papadamou (2013), Kollias, Papadamou, and Arvanitis (2013). 12.…”
Section: Notesmentioning
confidence: 99%
“…With the predominance of terrorism as one of the main international security threat, the number of papers that tried to test the impact of the terrorism on the capital market in terms of return and volatility has grown over time (Barros & Gil-Alana, 2009;Chesney, Reshetar, & Karaman, 2011). Some have found that terrorism has a negative impact on asset valuation, investment decisions, portfolio allocation; in addition to increasing volatility by affecting the market risk premium (Drakos, 2010;Chen & Siems, 2004;Kollias, Papadamou & Arvanitis, 2013).…”
Section: Introductionmentioning
confidence: 99%